THE EFFICACY OF H7 (SHENMEN) POINT ACUPRESSURE IN TREATING SLEEP DISORDERS PREGNANT WOMEN IN THIRD TRIMESTER (Proceedings OPTIMAL, 2025)
Pregnant women in the third trimester to experience discomfort, with sleep quality disorders being a notable manifestation. These disorders are typified by the frequency of nocturnal awakenings, which ranges from 3 to 11 times. 75% of pregnant women report a decline in sleep quality. The management of sleep quality disorders in pregnant women is recommended the utilization of non-pharmacological methods, such method being H7 (shenmen) acupressure. The objective of the study was to confirm the efficacy of H7 acupressure in addressing sleep quality disorders in pregnant women in the third trimester. The study was conducted in april 2023. The research is a pre-experimental design with a pretest and post-test design. The population of this study comprised pregnant women in third trimester who underwent examinations at independent midwife practices. Consecutive sampling was employed, with a total of 23 pregnant women. The data collection method employed was observation, with a questionnaire as the research instrument. The findings of the study demonstrated that sleep quality disorders in pregnant women in the third trimester demonstrated a significant improvement following the intervention. Prior to the intervention, the majority of sleep quality disorders were classified as poor, with 56.5%. However, following the intervention, a substantial proportion of sleep quality disorders were categorized as excellent, with 91.3% of cases demonstrating a notable improvement in sleep quality. It is hypothesized that midwives will be able to provide midwifery services that will help sleep quality disorders in pregnant women in the third trimester using H7 acupressure